2001
DOI: 10.1149/1.1377279
|View full text |Cite
|
Sign up to set email alerts
|

Composite Electrodeposition to Obtain Nanostructured Coatings

Abstract: Nanocomposite coatings are obtained by electrochemical deposition of silicon carbide nanoparticles (mean diameter 20 nm) in a nickel plating bath. The influence of nanoparticles on nickel electroplating is studied by electrochemical impedance spectroscopy at cathodic potential, and cathodic polarization diagrams are performed in the electrolyte with and without nanoparticles. We show that incorporation of 20 nm SiC particles into nickel deposits modifies the impedance and cathodic polarization diagrams in corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(75 citation statements)
references
References 10 publications
5
63
1
Order By: Relevance
“…In this case, the surfactant in the bath not only plays a role of dispersing agent for PTFE particles, but also acts as a brightener for the Ni-PTFE composite film. 11) In contrast to the results which have been found by other researchers, 12) the inclusion of PTFE particles does not remarkably affect the surface morphology of Ni-PTFE composite film (Fig. 7(c)) in comparison with Fig.…”
Section: (B))mentioning
confidence: 57%
“…In this case, the surfactant in the bath not only plays a role of dispersing agent for PTFE particles, but also acts as a brightener for the Ni-PTFE composite film. 11) In contrast to the results which have been found by other researchers, 12) the inclusion of PTFE particles does not remarkably affect the surface morphology of Ni-PTFE composite film (Fig. 7(c)) in comparison with Fig.…”
Section: (B))mentioning
confidence: 57%
“…Benea et al [35] showed that the incorporation of 20 nm SiC particles during Ni deposition modifies the impedance and cathodic polarization due to the modification of the surface morphology and crystallinity of the nickel matrix. Spinvalve-type multilayered structures in the form of nanowires were deposited by Fedosyuk et al [36] by pulsed ELD using a single electrolyte.…”
Section: Specific Advantages Of Electrochemical Depositionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Composite electrodeposits have been prepared by dispersing particles in the metal matrices. The co-deposition mechanism of particles was reported to be composed of two steps, namely, the adsorption of metal ions on the particles and the subsequent reduction of the adsorbed ions on cathode surfaces.…”
Section: Introductionmentioning
confidence: 99%